Materials for sustainable energy - Eldik, Rudi van; Macyk, Wojciech (Advances in inorganic chemistry, 2018)
Materials for Sustainable Energy, Volume 72, the latest release in the Advances in Inorganic Chemistry series presents timely and informative summaries on the current progress in a variety of subject areas. In this volume, concise, authoritative reviews provide updates on the photocatalytic generation of solar fuels (heterogeneous systems), Photocatalytic materials for energy and environment, The photoelectrocatalytic production of solar fuels, Artificial photosynthesis (homogeneous catalysis), The photocatalytic synthesis of chemicals, Dye sensitized solar cells, Supercapacitors, Lithium ion cells, Catalytic air purification (VOCs, soot), Catalytic air purification (NOx), and more.